Transformasi Digital UMKM Desa Kedaung: Strategi Penguatan Ekonomi Masyarakat - Ridwansyah; Nurmalia, Gustika; Mutiasari Nur Wulan; M Ammar Firas Wafiq (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid growth of the digital economy presents significant opportunities for strengthening the economic resilience of rural communities; however, many rural micro, small, and medium enterprises (MSMEs) continue to face constraints in digital literacy and technology utilization. This community service program aimed to enhance the digital capacity of MSME actors in Kedaung Village through structured training and intensive mentoring on digital literacy, online marketing, and digital payment systems. The program employed a Participatory Action Research (PAR) approach involving 30 MSME participants and was implemented through stages of needs assessment, training, mentoring, and evaluation. The results demonstrated a substantial improvement in participants’ digital literacy, with average scores increasing from 48% in the pre-test to 82% in the post-test. Furthermore, 67.5% of participants successfully established online marketplace accounts, 87.5% actively utilized social media for product promotion, and 50% adopted QRIS as a digital payment method. These findings indicate that practice-based training combined with continuous mentoring effectively accelerates digital adoption among rural MSMEs. The program contributes to the development of a sustainable digital village model by strengthening MSME competitiveness, expanding market access, and supporting inclusive rural economic growth. Keywords: digital literacy; rural community empowerment; MSMEs; digital economy; QRIS